Predicting the emission characteristics of VOCs in a simulated vehicle cabin environment based on small-scale chamber tests: Parameter determination and validation - Wang, Haimei; Zheng, Jihu; Yang, Tao; He, Zhangcan; Zhang, Peng; Liu, Xuefeng; Zhang, Meixia; Sun, Lihua; Yu, Xuefei; Zhao, Jing; Liu, Xiaoyu; Xu, Baoping; et al. (Environment international, 2020)
•The key parameters of VOCs from different vehicle cabin materials were measured.•Emission of acetaldehyde tops the list among the six VOCs for tested materials.•A model is developed to predict the emission and contribution of materials in cabin.•Good agreement is obtained between model predictions and chamber experiments. Volatile organic compounds (VOCs) emitted from vehicle parts and interior materials can seriously affect in-cabin air quality. Prior studies mainly focused on indoor material emissions, while studies of emissions in-cabins were relatively scarce. The emission behaviors of VOCs from vehicle cabin materials can be characterized by three key emission parameters: the initial emittable concentration (C0), diffusion coefficient (Dm), and partition coefficient (K). Based on a C-history method, we have performed a series of tests with a 30 L small-scale chamber to determine these three key emission parameters for six VOCs, benzene, toluene, ethylbenzene, xylene, formaldehyde, and acetaldehyde, from typical vehicle cabin materials, car roof upholstery, carpet, and seat. We found that acetaldehyde had the highest level in the gas-phase concentration and C0, which differs from residential indoor environments where formaldehyde is usually the most prevalent pollutant. The influence of temperature on the key emission parameters was also investigated. When the temperature rose from 25 °C to 65 °C, C0 increased by 40–640%, Dm increased by 40–170%, but K decreased by 38–71% for different material-VOC combinations. We then performed an independent validation to demonstrate the accuracy of the measured key emission parameters. Furthermore, considering that in reality, several materials coexist in vehicle cabins, we made a first attempt at applying a multi-source model to predict VOC emission behaviors in a simulated 3 m3 vehicle cabin, using the key emission parameters obtained from the small-scale chamber tests. The good agreement between the predictions and experiments (R2 = 0.82–0.99) demonstrated that the three key emission parameters measured via chamber tests can be scaled to estimate emission scenarios in realistic vehicle cabin environments. A pollution contribution analysis for the tested materials indicated that the car seat could significantly contribute to the total emissions.